Draft Genome Sequence of Enterobacter cloacae S23 a Plant Growthpromoting Passenger Endophytic Bacterium Isolated from Groundnut Nodule Possesses Stress Tolerance Traits - Ramakrishnan, Pavithra; Ariyan, Manikandan; Rangasamy, Anandham; Rajasekaran, Raghu; Ramasamy, Krishnamoorthy; Murugaiyan, SenthilKumar; Janahiraman, Veeranan (Current Genomics, 2023)
Aim: This study aims to reveal the passenger endophytic bacterium Enterobacter cloacae S23 isolated from groundnut nodules and to underpin the molecular mechanism and genes responsible for abiotic stress tolerance. Background: A variety of microorganisms that contribute to nodulation and encourage plant development activity in addition to the nodulating Rhizobium. Passenger endophytes (PE) are endophytes that accidentally penetrate the plant without any selective pressure keeping them in the interior tissue of the plant. PE possesses characteristics that encourage plant development and boost output while reducing pathogen infection and improving biotic and abiotic stress tolerance. However, there is a lack of molecular evidence on the passenger endophyte-mediated alleviation of abiotic stresses. Objective: This study was formulated to reveal the draft genome sequence of Enterobacter cloacae S23, as well as genes and characteristics involved in plant growth promotion and stress tolerance. Method: The data were submitted to PATRIC and the TORMES-1.0 Unicyclker tools were used to conduct a complete genome study of Enterobacter cloacae S23. The TORMES-1.0 platform was used to process the reads. RAST tool kit (RASTtk) was used to annotate the S23 sequence. The plant growth-promoting traits such as indole acetic acid production, siderophore secretion, production of extracellular polysaccharides, biofilm formation, phosphate solubilization, and accumulation of osmolytes were examined under normal, 7% NaCl and 30% polyethylene glycol amended conditions to determine their ability to withstand salt and moisture stressed conditions, respectively. Result: We report the size of Enterobacter cloacae S23 is 4.82Mb which contains 4511 proteincoding sequences, 71 transfer RNA genes, and 3 ribosomal RNA with a G+C content of DNA is 55.10%. Functional analysis revealed that most of the genes are involved in the metabolism of amino acids, cofactors, vitamins, stress response, nutrient solubilization (kdp, pho, pst, biofilm formation (pga IAA production (trp, siderophore production (luc, fhu, fep, ent, ybd, defense, and virulence. The result revealed that E. cloacae S23 exhibited multiple plant growth-promoting traits under abiotic stress conditions. Conclusion: Our research suggested that the discovery of anticipated genes and metabolic pathways might characterise this bacterium as an environmentally friendly bioresource to support groundnut growth through several mechanisms of action under multi-stresses.
Keywords: Endophytic bacteria